Kontekstualisasi Pendidikan Agama Kristen Bagi Remaja - Yulia Jayanti Tanama; Duma Fitri Pakpahan; Wahyu Sapta Purnama (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Adolescents tend to be critical about everything in their lives, including their religion and faith, so the right strategy is needed to convey the truths of the Bible that can be accepted logically and experienced in real life. Therefore, this research aims to implement contextual learning strategies in listening to PAK and contextuality in adolescence. This research method uses qualitative methods, interviews, observations, and documentation. The results of the research are that contextual learning strategies are strategies that are suitable for teenagers because they are engaging, increase knowledge, train critical thinking, and challenging to be able to analyze and can be applied in real terms to the physical, emotional, and interests of teenagers according to the truth of God's Word.